Kebijakan Pendidikan : Pemerataan dan Perluasan Akses ( Rehabilitasi Ruang Kelas Yang Rusak) - Fanny Puspasari Sianipar; Siti Tiara Maulia (Pusat Riset dan Inovasi Nasional, 2023)
Education is one of the important things that can affect the progress of a country. The school building is an essential part of organizing teaching and learning activities. Routine care and maintenance can maintain the quality of school buildings, so they can be used safely and comfortably. Development uses funds provided by the regional government and the central government in the form of special allocation funds (DAK). Seeing how the quality of educational infrastructure is one of the problems of education in Indonesia. While the quality of education infrastructure in Indonesia is still considered low, the renovation of school buildings has increased students' enthusiasm for learning. Indonesian children have a high enthusiasm for learning, therefore we should not let their enthusiasm and smiles fade from their faces just because the development of education in Indonesia is uneven.